1990
DOI: 10.1063/1.458462
|View full text |Cite
|
Sign up to set email alerts
|

The vinyl radical investigated by infrared diode laser kinetic spectroscopy

Abstract: A c-type band was observed at around 895 cm−1 by infrared diode laser kinetic spectroscopy combined with the excimer laser photolysis of vinyl halides at 193 nm and was assigned to the CH2 wagging mode of the vinyl radical. The band was found to consist of two component bands separated by 0.0541(11) cm−1. Both component bands showed clearly the statistical weight in an alternative way, that is, if one shows the weight 1:3 for even:odd Ka levels, the other exhibits 3:1, indicating that the radical is of C2v eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 13 publications
4
58
1
Order By: Relevance
“…Electronic mail: tanakscc@mbox.nc.kyushu-u.ac.jp the isotope effect. 4 Kanamori et al 18 observed the same infrared band by high-resolution diode laser kinetic spectroscopy combined with the 193 nm excimer laser photolysis of vinyl halides, and confirmed that it corresponds to the CH 2 wagging mode because of the c-type selection rules obeyed by the transitions. They found that the band consists of two component bands ͑sym and antisym͒ separated by about 0.054 cm Ϫ1 .…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Electronic mail: tanakscc@mbox.nc.kyushu-u.ac.jp the isotope effect. 4 Kanamori et al 18 observed the same infrared band by high-resolution diode laser kinetic spectroscopy combined with the 193 nm excimer laser photolysis of vinyl halides, and confirmed that it corresponds to the CH 2 wagging mode because of the c-type selection rules obeyed by the transitions. They found that the band consists of two component bands ͑sym and antisym͒ separated by about 0.054 cm Ϫ1 .…”
Section: Introductionmentioning
confidence: 81%
“…[1][2][3] Extensive studies on the structure of the vinyl radical, both theoretical 4 -12 and experimental, [13][14][15][16][17][18][19][20][21][22][23][24] have been published, but spectroscopic studies have been quite limited due to difficulty in producing the radical at a high enough concentration. A particularly interesting feature of the vinyl radical is the intramolecular transfer of the proton in the CH group ͑␣ proton͒ as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of such large amplitude H atom exchange dynamics in forming vinyl radical is strongly reminiscent of the "roaming" H atom behavior noted by Suits, Bowman and coworkers in near threshold studies of formaldehyde photolysis, 148,149 as well as studies of acetaldehyde photolysis of Kable and Houston. 150 It is particularly interesting that alternate generation of vinyl radical in these same 0 + and 0 − states via 193 nm photolysis of vinyl bromide yields the "normal" 3:1 nuclear spin intensity alternation associated with feasible exchange of the 2 H atoms on the CH 2 group, as first verified by Kanamori et al,146 This suggests that there may be multiple dynamical pathways for formation of vinyl, depending on degree of internal vibrational excitation left in the nascent radical species by either photolytic bond cleavage or dissociative electron attachment processes. Detailed exploration of such intriguing dynamical processes would clearly be accelerated by development of a high level ab initio vinyl potential energy surfaces in full dimensionality, which we hope the current work will stimulate.…”
Section: Vinyl Radical: Tunneling and H-atom "Roaming"mentioning
confidence: 87%
“…This radical center also permits a relatively low energy in plane pathway for motion of the lone α-CH bond from one side to the other, which therefore raises the interesting possibility of large amplitude tunneling dynamics, or alternatively, intramolecular H atom transfer, that would be apparent in high resolution studies. Indeed, Kanamori et al 146 reported the first high-resolution infrared spectroscopy of the CH 2 wagging mode of the vinyl radical near 895 cm −1 , with a 3:1 (1:3) nuclear spin statistical alternation for K a = even:odd levels in the ground and excited tunneling states, respectively. This is to be expected due to the two H atoms (I = 1/2) in the CH 2 moiety, which become equivalent under high resolution detection conditions by feasible tunneling of the α-CH across a C 2v transition state geometry.…”
Section: Vinyl Radical: Tunneling and H-atom "Roaming"mentioning
confidence: 98%
“…One good example is the vinyl radical, which plays an important role in some reactions of organic molecules. Kanamori et al (65) successfully produced this molecule by the photolysis of vinyl halides. He also tried to obtain this transient molecule by discharge, but failed; the molecule seems to be too fragile to generate by such severe methods as discharge.…”
Section: Further Remarks and The Futurementioning
confidence: 99%